Crowdfunding preferences for a sustainable milk product with integrated photovoltaic water pumping system in China - Zhang, Chi; Campana, Pietro Elia; Liu, Chengxi; Wang, Ke; Yan, Jinyue (Applied energy, 2019)
•Evaluated a novel crowdfunding financing mechanism for PVWP with milk production.•Feasibility analyses with DCM on crowdfunding intentions and willingness-to-pay.•Environmental consciousness, child, female are crucial to crowdfunding intentions and WTP.•Online pre-sale purchases trends encourage customers crowdfunding sustainable products. This paper studies the role of potential investors in financing renewable energy systems—specifically, relating to crowdfunding as a financing mechanism, with the enhancement of internet and social-media tools. The research question in this study is whether crowdfunding with a novel socio-technical product reward program attracts potential customers to a more sustainable milk product with a specific integrated photovoltaic water pumping (PVWP) system. The particular case study we empirically investigated is product reward crowdfunding in dairy milk production in China. The milk production chain was supplied by PVWP system integration, which generated solar energy both for feed production for dairy cows and for the operation of dairy farms. 48 semi-structured in-depth interviews were conducted between the research team and customers in order to perform qualitative analyses of the determinants of customers’ milk purchase behaviors. In addition, 357 online surveys were collected for quantitative analysis. Binary and ordered probit regressions were employed to use survey date to systematically estimate purchase intention and willingness-to-pay for sustainable milk. Customer behaviors, environmental consciousness, and individual socio-demographic factors were investigated as potential explanatory variables. Over 82% of the survey participants showed intentions to purchase the sustainable milk with the PVWP system. In the survey and interview samples, results showed that milk quality, nutrition improvement, emissions reduction, and environmental benefits attributed to the integrated PVWP system were the major factors considered by interviewees who showed intentions to purchase the crowdfunded dairy milk. Regression model results suggested that potential customers with higher income levels, and those of parenting age, and those with young children or planning to have children, had a higher willingness-to-pay than other customers for the crowdfunded sustainable dairy milk. The familiarity with and popularity of online shopping and pre-sale purchases in China made customers more open to and proactive towards pre-pay and crowdfunding mechanisms. This article evaluated key factors which may influence potential customers for crowdfunding, and used a discrete choice model to estimate customers’ willingness-to-pay for reward-based projects. These results could help producers of sustainable milk products to identify potential target groups in China and estimate market demand. This exploratory study could provide a framework with both quantitative and qualitative assessment of crowdfunding for renewable energy systems in a national or international context.